THE IMPACT OF INDEPENDENT CURRICULUM TRAINING AND THE INDEPENDENT TEACHING PLATFORM ON TEACHER PERFORMANCE THROUGH TEACHER COMPETENCEAT STATE VOCATIONAL SCHOOL 2 BENER MERIAH - Maroli Putra; Sri Rahayu; Elfitra Desy Surya (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of the Independent Curriculum training and the use of the Merdeka Mengajar Platform on teacher performance through teacher competency as a mediating variable at SMK Negeri 2 Bener Meriah. Changes in national education policy encourage teachers to adapt to more flexible and student-centered learning approaches. The Independent Curriculum training and features within the Independent Teaching Platform, such as self-paced training, teaching tools, and inspirational videos, are expected to improve teachers' pedagogical and professional competencies. This study used a quantitative approach with path analysis techniques. The study population was all teachers at SMK Negeri 2 Bener Meriah, with samples taken proportionally. The results showed that the Independent Curriculum training and the use of the Merdeka Mengajar Platform had a positive and significant effect on teacher competency, and teacher competency significantly influenced teacher performance. In addition, teacher competency also played a mediating role in strengthening the relationship between training and teacher performance. These findings emphasize the importance of continuous training and the use of educational technology to support teacher professionalism in the Independent Curriculum era.